PRAKTEK PENGUNGKAPAN SUSTAINABILITY REPORT DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Okta Agil Widodo (Program Studi Manajemen, 2019)
This study aimed to analyze the influence of the characteristics of the company and corporate governance disclosure of sustainability reports. Methods of sampling in this study using purposive sampling method in banking companiesin Indonesia Stock Exchange (IDX) during the years 2013-2017. As many as 34 companies are used as the population in the study produced 28 companies that the research sample. This research uses multiple regression. The result showed that the result of this study that significant profitability on the disclosure of sustainability reports, liquidity is not significant to the disclosure of sustainability reports, leverage is not significant to the disclosure of sustainability reports, activity ratio is not significant to the disclosure of sustainability reports, audit committee significant to the disclosure of sustainability reports, board directors significant to the disclosure of sustainability reports, governance committee significant to the disclosure of sustainability reports and firm size is not significant to the disclosure of sustainability reports.